Ultrafast One-Photon (232 vs 266 nm) Bond-Selective Photochemistry of Bromoiodomethane (CH2BrI) in Solution - Panov M. S.; Mereshchenko A. S.; Butaeva E. V.; Tarnovsky A. N. (EPJ Web of Conferences, 2013)
Ultrafast broadband transient absorption spectra measured from the deep-ultraviolet to the near-infrared region following single-photon excitation of bromoiodomethane in acetonitrile at different wavelengths manifest chromophore -selective structural rearrangement and carbon-halogen bond dissociation in solution.